2019
DOI: 10.1080/15592294.2019.1700004
|View full text |Cite
|
Sign up to set email alerts
|

DNA hydroxymethylation increases the susceptibility of reactivation of methylated P16 alleles in cancer cells

Abstract: It is well established that 5-methylcytosine (5mC) in genomic DNA of mammalian cells can be oxidized into 5-hydroxymethylcytosine (5hmC) and other derivates by DNA dioxygenase TETs. While conversion of 5mC to 5hmC plays an important role in active DNA demethylation through further oxidation steps, a certain proportion of 5hmCs remain in the genome. Although 5hmCs contribute to the flexibility of chromatin and protect bivalent promoters from hypermethylation, the direct effect of 5hmCs on gene transcription is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The mRNA expression level was upregulated in CRC tissue, which was associated with a poor prognosis in CRC patients. It is reported that DNA hydroxymethylation increases the susceptibility to reactivation of methylated P16 alleles in cancer cells, and 5-hmc may play an important role in gene transcription [ 37 ]. This may partly explain our research that LCN2, LRG1, S100P, and TACSTD2 DNA hydroxymethylation levels were positively correlated with their mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression level was upregulated in CRC tissue, which was associated with a poor prognosis in CRC patients. It is reported that DNA hydroxymethylation increases the susceptibility to reactivation of methylated P16 alleles in cancer cells, and 5-hmc may play an important role in gene transcription [ 37 ]. This may partly explain our research that LCN2, LRG1, S100P, and TACSTD2 DNA hydroxymethylation levels were positively correlated with their mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant methylation and demethylation have been linked to pathogenesis of diseases, such as cancers, neurodegenerative disorders, and others (heart, liver, kidney, lung, and immunological disorders) [34][35][36][37]. Of the main components in the machinery for cytosine modifications, TET family members shape the landscape of the epigenome via regulation and disposition of 5-hmC levels [38,39] and distinctly function as regulators for brain development as well as suppressors and promoters for tumorigenesis [26,[40][41][42][43][44][45][46] (Tables 1,2,3,4, Ref. [15,[34][35][36][37]).…”
Section: Common Chemical Functions Of Tet Proteins Referencesmentioning
confidence: 99%